K Karakteristik Magnetic Biochar Sebagai Adsorben Untuk Pemanfaatan Kembali Buangan Akhir POME Untuk Air Baku Industri - Kesni savitri savitri (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2022)
The current problem in the Palm oil industry is POME's final discharge failed to comply with discharge standards. This study aims to treat POME final discharge using magnetic biochars (MBC) and treated water can be reused as raw water for the palm oil industry. MBC were successfully produced from palm fronds through the pyrolysis process together with FeCl3.6H2O modification. MBC were characterized by acquiring elemental, functional groups, morphological and magnetic properties of adsorbent. The characterization showed embedded iron oxide crystals within the biochar structure with a magnetic strength of 12,14 emu/g which can assist the separation process of the powdered adsorbent from the treated water. The highest removal of COD, TSS, and color was 72.72%, 77.95%, and 84.30%, respectively with an 8.55 g/l magnetic biochar dosage and 150 minutes contact time. However, the results of the final POME effluent treatment have not all of the parameters reached the industrial water quality standard class 3.